Discovery of a new class of triazole based inhibitors of acetyl transferase KAT2A. (31st December 2022) - Pacifico, Roberta; Del Gaudio, Nunzio; Bove, Guglielmo; Altucci, Lucia; Siragusa, Lydia; Cruciani, Gabriele; Ruvo, Menotti; Bellavita, Rosa; Grieco, Paolo; Adamo, Mauro F. A.
Abstract: We have recently developed a new synthetic methodology that provided both N -aryl-5-hydroxytriazoles and N -pyridine-4-alkyl triazoles. A selection of these products was carried through virtual screening towards targets that are contemporary and validated for drug discovery and development. This study determined a number of potential structure target dyads of which N -pyridinium-4-carboxylic-5-alkyl triazole displayed the highest score specificity towards KAT2A. Binding affinity tests of abovementioned triazole and related analogs towards KAT2A confirmed the predictions of the in-silico assay. Finally, we have run in vitro inhibition assays of selected triazoles towards KAT2A; the ensemble of binding and inhibition assays delivered pyridyl-triazoles carboxylates as the prototype of a new class of inhibitors of KAT2A.